(untitled) (The Planet, 2023)
Introduction: Laparoscopic surgery is one of the pillarsof modern surgical care. Benefits include decreasedpostoperative pain and quicker return to normal activityminimizing the financial burden to the patient. There are,some unique complications associated with gaining accessto the abdomen for laparoscopic surgery. Aim of thestudy: The aim of the study was to determine the incidenceof early postoperative port site complications followinglaparoscopic surgery and their causes. Methods andmaterials: This prospective observational study wasconducted at the Department of Surgery, BIRDEM GeneralHospital, Shahbag, Dhaka, Bangladesh. The studyduration was 1 year, from January 2019 to December2019. A total of 700 patients undergoing laparoscopicsurgery were studied during the above-mentioned period.The patients were observed at several intervals up to 6 months. Results: Regarding port sitecomplications, the majority 29.3% patients had port site infection, 19.5% port site bleeding, 7(17.1%) peri-umbilical bruising, and 12.1% port-site incisional hernia 9.1%, 9.1% and 9.1%had altered port site sensation, tuberculosis, and hypertrophied scar respectively. 4.9% and4.9% patients had chronic discharging sinus and foreign body granuloma respectively.Instrument & peri-operative sterility, foreign body reaction, diabetes mellitus, and othercomorbidities were major causes of complications. Conclusion: Laparoscopic surgery itselfhas many risks common with any surgery but port site complications in particular, althoughinfrequent, are bothersome complications which undermine the benefits of minimal invasivesurgery. Common complications at the port site include infection, bleeding, peri-umbilicalbruising, and rarely, incisional hernia.